2010
DOI: 10.1176/appi.ps.61.7.690
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences and Similarities in Outpatient Treatment for Depression in the Netherlands

Abstract: There are widespread concerns about disparities in mental health treatment for ethnic minority groups. However, previous research in this area has been limited mainly to the United States and Great Britain, raising doubts about the external validity with respect to other European countries. This study addressed ethnic differences in characteristics of outpatient treatment for depression in the Netherlands. Methods: Longitudinal data (2001-2005) were extracted from a nationwide psychiatric case register. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(39 reference statements)
1
5
1
Order By: Relevance
“…Thus, the results of this study do not support the general idea that non-Western ethnic minority patients are less likely to receive guideline-concordant care for CMD. And as such, these results are quite in line with several other recent studies from the Netherlands, which paint a more optimistic picture regarding ethnic minority patients in mental health care [65][66][67][68]. Without thus trying to ignore the statistically significant unfavorable associations which we did find, we believe it is important to acknowledge that the Netherlands -like many other Western countries -nowadays has a considerable history of adapting (mental) health services to suit clients from different cultures [69,70].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the results of this study do not support the general idea that non-Western ethnic minority patients are less likely to receive guideline-concordant care for CMD. And as such, these results are quite in line with several other recent studies from the Netherlands, which paint a more optimistic picture regarding ethnic minority patients in mental health care [65][66][67][68]. Without thus trying to ignore the statistically significant unfavorable associations which we did find, we believe it is important to acknowledge that the Netherlands -like many other Western countries -nowadays has a considerable history of adapting (mental) health services to suit clients from different cultures [69,70].…”
Section: Discussionsupporting
confidence: 90%
“…Since the 1970s, Surinamese migrants have arrived in the Netherlands as well, because of unfavorable economic circumstances in Suriname. As Suriname is a former Dutch colony, most of these migrants master the Dutch language (Fassaert, 2011). According to research in the Dutch general population, Surinamese migrants show the highest degree of cultural adaptation, followed by Moroccan migrants and then by Turkish migrants (Kamperman, Komproe, & De Jong, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several explanations have been suggested, including inappropriate help-seeking behaviour, under-detection, cross-cultural diagnostic difficulties and inappropriate treatment (Fassaert et al, 2009a;Kirmayer, 2001;Simon et al, 2002;Swinnen and Selten, 2007). Recent studies in the Netherlands have shown comparable access and largely comparable administrative indicators (frequency of visits, drop-out) of psychiatric treatment of ethnic minority patients with depressive or anxiety disorders (Fassaert et al, 2009b(Fassaert et al, , 2010. In the USA, decline in ethnic disparities in detection and treatment of these common mental disorders has also been noticed (Stockdale et al, 2008).…”
Section: Discussionmentioning
confidence: 99%